Outcomes of 23- and 25-gauge transconjunctival sutureless vitrectomies for idiopathic macular holes. Issue 9 (9th July 2008) - Kusuhara, S; Ooto, S; Kimura, D; Itoi, K; Mukuno, H; Miyamoto, N; Akimoto, M; Kuriyama, S; Takagi, H
Abstract : Background/aims: To assess the outcomes of 23-gauge sutureless transconjunctival vitrectomies (TSV), as compared with 25-gauge TSV in macular hole surgeries. Methods: A retrospective, consecutive, interventional case series of 47 eyes with idiopathic macular holes treated by 23- or 25-gauge TSV were analysed. Results: The operative time was 37.2 (SD 8.9) min with 23-gauge TSV and 34.2 (8.7) min with 25-gauge TSV (p = 0.388). The anatomical success rate was 96% with 23-gauge TSV and 92% with 25-gauge TSV (p>0.999). The logarithm of the minimum angle of resolution of best-corrected visual acuity (BCVA) at the sixth postoperative month was 0.19 (0.16) with 23-gauge TSV and 0.19 (0.25) with 25-gauge TSV (p = 0.521). Postoperative improvement in BCVA was comparable between the two TSVs. IOP on postoperative day 1 was lower with 25-gauge TSV (12.3 (4.9) mm Hg) than with 23-gauge TSV (17.4 (5.8) mm Hg) (p = 0.036). Complications included retinal break, intraoperative bleeding and slippage of the infusion cannula with 23-gauge TSV, while retinal detachment and postoperative hypotony occurred in the 25-gauge TSV group (p = 0.570). Conclusion: 23-gauge TSV appears to be as safe and effective as 25-gauge TSV in macular hole surgery.